The metadata schema design and utility architecture for Thai Lanna inscription collection - Techawut C. (2014)
Digitization has been applied to the Thai Lanna script, or so-called the Fakkham script. Two major requirements to create a digital collection of the Thai Lanna inscriptions is to preserve them in the digital format and to infer for the engraving period of each inscriptions supporting the linguists and historians to interpret the contents within an appropriate context. The digital inscription images can be processed by the image processing techniques to create an important output, a set of each character images. It does not only use for a data set training in a preservation process, but also indicate the evolution of ancient characters, character relationships and stories in the historical times. This paper presents two key issues. First, the creation of metadata schema for the output describing Thai Lanna inscriptions and storing a set of character images by reusing and extending the metadata schema from Thai Lanna archives. Second, the architecture of utilization showing the contributions of our metadata schema design that serves as the foundation of the architecture. © Springer International Publishing 2013.